The Potential Role of the NLRP3 Inflammasome Activation as a Link Between Mitochondria ROS Generation and Neuroinflammation in Postoperative Cognitive Dysfunction - Wei, Penghui; Yang, Fan; Zheng, Qiang; Tang, Wenxi; Li, Jianjun (Frontiers in Cellular Neuroscience, 2019)
Postoperative cognitive dysfunction (POCD) is commonly observed in perioperative care following major surgery and general anesthesia in elderly individuals. No preventive or interventional agents have been established so far. Although the role of interleukin (IL)-1β-mediated neuroinflammation following surgery and anesthesia is strongly implicated in POCD, the exact mechanism of action remains to be explored. Growing evidence has shown that mitochondria-derived reactive oxygen species (mtROS) are closely linked to IL-1β expression through a redox sensor known as the nod-like receptor pyrin domain-containing 3 (NLRP3) inflammasome. Therefore, we hypothesize that the mechanisms underlying POCD involve the mtROS/NLRP3 inflammasome/IL-1β signaling pathway. Furthermore, we speculate that cholinergic anti-inflammatory pathway induced by α7 nicotinic acetylcholine receptor may be the potential upstream of mtROS/NLRP3 inflammasome/IL-1β signaling pathway in POCD. For validating the hypotheses, we provide experimental plan involving different paradigms namely; microglial cells and behavioral studies. The link between mtROS, the NLRP3 inflammasome, and IL-1β within and between these different stages in combination with mtROS and NLRP3 inflammasome agonists and inhibitors could be explored using techniques, such as knockout mice, small interference ribonucleic acid, flow cytometry, co-immunoprecipitation, and the Morris Water Maze test. We conclude that the NLRP3 inflammasome is a new preventive and therapeutic target for POCD.